The general characteristics and organic matters of therapeutic mud from Lake Noot (Mongolia) - Gankhurel, Ganzaya; Byambajav, Nomintsetseg; Batnasan, Bayaraa; Gania, Dolmaa (Mongolian Journal of Chemistry, 2021)
In this investigation, we examined the chemical composition, physicochemical properties, and organic matter of therapeutic mud from Lake Noot in the Arkhangai province of Mongolia. The therapeutic mud from “Lake Noot” is used in the pelotherapy of local health care services for some time but without deep characterization. Due to this, a study of therapeutic mud samples was required. Our research concentrated on identifying general characteristics, organic matter, mineralogical, and chemical composition of therapeutic mud at two different Lake Noot sites. Results showed that the therapeutic mud belongs to the continental hydrogen sulfide sticky mud type. The total organic matter in the therapeutic mud of Lake Noot was 14.44%. Total organic matter contains a humic substance of 42.17%, lipid 16.62%, and carbohydrate 7.13%. A total of 172 compounds were identified in the dissoluble organic matter of therapeutic mud, mainly of natural origin, using the gas chromatography-mass spectrometry (GC/MS) method. The dominant compounds were saturated and unsaturated hydrocarbons with 13–44 carbon atoms and carboxylic acids and their ethers. Some of the identified organic compounds have been reported antimicrobial, anti-inflammatory, antibacterial, and antifungal properties.